Sperm motility in baseline spermogram is predictive of total motile sperm after preparation for insemination - Ayala A., F.; Morales, A.; Merino, M.; Juarez, B. L.; Absalon, L.; Enrique, G. (2007)
Every institution has diferent cut-off values to determine which is the required amount of total motile sperms after preparation for intrauterine insemination. In our center we consider 3 million total motile sperm as the minimum necesary to consider the sample as appropiate. The objective of this study is to determine whether sperm motility in baseline spermogram is predictive of total motile sperm count after sperm preparation for insemination.